Macroeconomic podcasts: teaching the internet generation. (14th July 2021) - Vidal, Daniel Diaz
Economics instructors continue to move away from the traditional 'chalk and talk' style of teaching, to more inventive and appealing pedagogical strategies that better fit the educational needs and preferences of the newer generations of learners. This paper furthers this trend by suggesting the use of podcasts to teach a set of core concepts and theories commonly learned in any introduction to macroeconomics course. The paper introduces six podcasts and a list of associated economic theories and concepts that can be related to specific parts of each podcast. Furthermore, the paper offers the reader a set of examples and recommendations regarding how to specifically use four of these podcasts in the classroom. The paper invites the reader to use the podcasts and the recommendations provided in the hope that she/he will also generate and publicise her/his own examples moving forward.